q=m * Cs * triangle T or q=m * Cs * (T_f - T_i) Solve for T_f.

Lillie Pittman 2022-07-31 Answered
q = m C s T
or
q = m C s ( T f T i )
Solve for T f .
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

uavklarajo
Answered 2022-08-01 Author has 17 answers
q = m C s ( T f T i )
Divide by mCs and you get the following
q m C s = T f T i
Add initial T (subscript "i") to both sides and you get
q m C s + T i = T f
Not exactly what you’re looking for?
Ask My Question
Quessyrutty6w
Answered 2022-08-02 Author has 3 answers
q = m C s ( T f T i )
so T f T i = q / m C s
T f = T i + q / m C s
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

New questions